2020
DOI: 10.31234/osf.io/e3jvq
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Mental imagery and visual working memory abilities appear to be unrelated in childhood: evidence for individual differences in strategy use

Abstract: We addressed three research gaps related to Mental imagery (MI) in children. First, MI relies on depictive representations in adults, however evidence for a depictive theory of MI in children is lacking. Second, researchers have employed a four sub-component model (Image Generation, Image Maintenance, Mental Rotation, Image Scanning) to investigate the development of MI, however findings are mixed. Finally, shared mechanisms between MI and Visual Working Memory (VWM) are suggested in adult literature, yet this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
1

Year Published

2020
2020
2021
2021

Publication Types

Select...
1
1

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(15 citation statements)
references
References 52 publications
(95 reference statements)
0
14
1
Order By: Relevance
“…Recent research has extended previous findings by adapting a battery of tasks to investigate individual differences in the visual precision of MI developmentally throughout the primary school years, i.e. from what age can children generate and manipulate images of high visual precision (Bates & Farran, 2020). In this study it was found that children from the youngest age tested (age 6 years) can generate and maintain highly visual mental images and these skills reach adult-like levels at approximately age 8 years in Image Generation and approximately age 10 years in Image Maintenance.…”
Section: Mental Imagerymentioning
confidence: 84%
See 4 more Smart Citations
“…Recent research has extended previous findings by adapting a battery of tasks to investigate individual differences in the visual precision of MI developmentally throughout the primary school years, i.e. from what age can children generate and manipulate images of high visual precision (Bates & Farran, 2020). In this study it was found that children from the youngest age tested (age 6 years) can generate and maintain highly visual mental images and these skills reach adult-like levels at approximately age 8 years in Image Generation and approximately age 10 years in Image Maintenance.…”
Section: Mental Imagerymentioning
confidence: 84%
“…In this study it was found that children from the youngest age tested (age 6 years) can generate and maintain highly visual mental images and these skills reach adult-like levels at approximately age 8 years in Image Generation and approximately age 10 years in Image Maintenance. Moreover, the spatial accuracy of visual representations (Image Scanning) and how efficiently representations are transformed (Mental Rotation) were present from the youngest age tested (age 6 years) (Bates & Farran, 2020). Evidence has largely found that the sub-components of MI are not correlated in childhood (Bates & Farran, 2020;Kosslyn et al, 1990) supporting Kosslyn's separable-component model.…”
Section: Mental Imagerymentioning
confidence: 93%
See 3 more Smart Citations